Genome-wide association study identifies variants in HORMAD2 associated with tonsillectomy. Issue 5 (9th December 2016) - Feenstra, Bjarke; Bager, Peter; Liu, Xueping; Hjalgrim, Henrik; Nohr, Ellen A; Hougaard, David M; Geller, Frank; Melbye, Mads
Abstract : Background: Inflammation of the tonsils is a normal response to infection, but some individuals experience recurrent, severe tonsillitis and massive hypertrophy of the tonsils in which case surgical removal of the tonsils may be considered. Objective: To identify common genetic variants associated with tonsillectomy. Methods: We used tonsillectomy information from Danish health registers and carried out a genome-wide association study comprising 1464 patients and 12 019 controls of Northwestern European ancestry, with replication in an independent sample set of 1575 patients and 1367 controls. Results: The variant rs2412971, intronic in HORMAD2 at chromosome 22q12.2, was robustly associated with tonsillectomy (OR=1.22; p=1.48×10 –9 ) and is highly correlated with SNPs previously found to be associated with IgA nephropathy, Crohn's disease (CD) and early onset inflammatory bowel disease (IBD). The risk allele for tonsillectomy corresponded to increased risk of IgA nephropathy and decreased risk of CD and IBD. We further performed lookup analyses of the top SNP for outcomes related to tonsillectomy in the combined discovery and replication sample and found that rs2412971 was associated with acute tonsillitis (OR=1.19; p=7.82×10 –4 ), chronic disease of the tonsils (OR=1.19; p=2.32×10 –6 ) and appendectomy (OR=1.18; p=1.13×10 –3 ). Conclusions: We identified and replicated a genetic association at 22q12.2 with tonsillectomy. Further functional investigation is required to illuminate whether the molecular mechanisms underlying the genetic association involve general lymphoid hyper-reaction throughout the mucosa-associated lymphoid tissue system.